Ecological and environmental physiology of birds - Bicudo, J. Eduardo P. W.; Buttemer, William A.; Chappell, Mark A. (Oxford : Oxford University Press, 2010)
Examining avian physiology in detail, this text specifically addresses the unique physiological characteristics of birds, although experimental techniques and future research directions are also considered.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Birds -- Ecophysiology